Framingham risk scores and anthropometric measurements in predicting cardiovascular risks among Malay men - Moy, Foong Ming; Ab Sallam, Atiya; Wong, M.L. (2008)
Framingham Risk Scores is an established method to predict an individual's 10-year risk for coronary heart disease (CHD). It provides a more precise delineation of risk which might lead to appropriate selection of therapy and opportunities for patient education and motivation. A Healthy Lifestyle Project was initiated to decrease the modifiable risk factors for CHD in a worksite in Kuala Lumpur. The participants were Malay men (n=186) working as security guards in a public university. Their mean age was 46.6 Â± 6.6 years. The majority had secondary education and were married. The participants' 10-year risks based on the Framingham Risk Scores were 55.4, 39.8 and 4.8 respectively for categories of low (<10), intermediate (10 to 20) and high (>20) risk. Their Framingham Risk Scores were then correlated with anthropometric measurements such as the Body Mass Index (BMI), waist circumference and waist-hip-ratio (WHR). All the anthropometric measurements had weak but significant correlation with the Framingham Risk Scores (WHR: r=0.26; waist circumference: r=0.23; BMI: r=0.16). In conclusion, 44.6 of our participants had more than 10 risk in developing CHD in the coming ten years. Hence, they are suitable target candidates for the promotion of a healthy lifestyle such as smoking cessation, weight control, healthy dietary patterns and increased physical activities. Indicators of abdominal obesity like WHR or waist circumference may be used to complement the Framingham Risk Scores for the prediction of CHD risk in this population.